Analysis of the Influence of Dividend Policy and Investment Decisions on the Share Prices of IDX Manufacturing Companies 2019–2023 - Nova Dwiyanti; Eko Giyartiningrum (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the implications of the existence of the Indonesian National Cooperative Council (Dekopin) in the context of national cooperative development. Using a qualitative descriptive method with a normative juridical approach, this research explores the legal, institutional, and operational aspects of Dekopin following the issuance of Law Number 11 of 2020 concerning Job Creation. The study finds that Dekopin's current structure raises legal questions regarding its institutional legitimacy, especially with the establishment of two competing organizational versions, which contradict the principles of cooperative unity and the Indonesian Cooperative Law. The results reveal that the government's ambiguity in enforcing legal clarity has led to confusion among cooperative actors and weakened the cooperative movement. This research suggests that the government needs to immediately revise or provide legal certainty regarding Dekopin's institutional status to strengthen the cooperative sector's governance and unity. The study also highlights the need for a more inclusive and democratic cooperative representation to ensure the optimal realization of cooperative development in Indonesia.